Cyberterrorism in Colombian Legislation: An Analysis from Criminology - Nicolaysen Sanchez, Hans; Castellanos Peña, María Paula; Sierra-Zamora, Paola Alexandra; Bermúdez-Tapia, Manuel (Law, State and Telecommunications Review, 2024)
[Purpose] The globalization of post-industrial society has generated new figures that govern traditional human relations such as social, political, economic and financial customs in the last thirty years. The development of new challenges is evaluated in the economic, political, social and legal field, in particular because the concepts and normative field are surpassed by the extraterritoriality of the phenomena that take place in the field of transnational crime. This new modality of execution of crimes represents a severe problem for national jurisdictions and sovereignties because it subjugates criminal phenomenology and affects criminal law, limiting it not only in a normative sphere but also in a theoretical and procedural perspective because its evaluation and subsequent judgment implies a series of limiting conditions for States and especially governments that may be affected by a cyberattack caused by governments or criminal groups that may cause effects that affect the administrative structure of a country or may cause an economic effect that may generate a severe weakening of Defense and National Security. [Methodology/Approach/Design] For this reason, this work emphasizes the legal and dogmatic analysis of cyberterrorism in order to detail its characteristics and develop the analysis of its regulation in the Colombian legislative framework through the hypothesis: The development of technology in today’s society allows the amplification of the use of new communication systems and access to information within cyberspace where various actions can be generated that can constitute serious damage to the development of the ordinary activities of a country, of a community, of a company or network of companies that negatively affects the social, democratic and governance spheres of a country, causing uncertainty in the population, exceeding the regulatory framework of national legislation. [Findings] In short, it was possible to determine that within the Colombian legal regulation, specifically in its penal code, the crime of cyberterrorism is not tacitly typified. Owing to this fact, the findings achieved from this document led to a careful reflection about the impact of cyberterrorism on personal and national security, so it encourages the Colombian legislation interest to regulate and punish those criminal behaviors in cyberspace and, consequently, to provide guarantees under the constitutional principles of law for cyber victims and cyber criminals.